Pharmacology of restless legs syndrome (RLS) - Clemens, Stefan; Ghorayeb, Imad; Enna, S. J.; Lecount, Lynn (Advances in pharmacology (San Diego, Calif.), 2019)
'Pharmacology of Restless Legs Syndrome (RLS), ' Volume 84 in the Advances in Pharmacology series, presents a variety of chapters from the best authors in the field on essential topics, with this volume presenting chapters on Targeting the adenosinergic system in Restless Legs Syndrome, Assessing iron uptake mechanisms in the brain: impact of gender and genotype, Pharmacological treatments of RLS in augmentation, C. elegans and its applicability to studies on RLS, The neurophysiology of hyperarousal in RLS: hints for a role of glutamate/GABA, Treatment management and options in RLS patients, Pharmacological responsiveness of Periodic Legs Movements during Sleep, and more. --